In pursuit of Shinzo Abe`s Olympic dream? Olympics in Japan`s 2020 politics - Rozmiarek, M. (Summer Olympic Games Tokyo 2020 facing the Coronavirus COVID-19 pandemic, 2021)
For Shinzo Abe, the longest-serving Prime Minister of Japan and leader of the Liberal Democratic Party, the organization of the Games of the XXXII Olympiad in Tokyo in 2020 was to be the main symbol of the country`s reconstruction. A careful examination of press notes, announcements, articles, columns, and expert analyses published between January 1 and August 31, 2020, in The Japan Times regarding the policies of the Japanese government showed that its aims were to inaugurate Reiwa, i.e. a new Japanese era, under the motto "Reconstruction Olympics" and to implement many social and political reforms necessitated for years. Although the Prime Minister himself showed a deep personal commitment to the preparation process before the Olympics at every stage, the COVID-19 pandemic entirely thwarted his plans. In March 2020, after long consultations with the International Olympic Committee, Shinzo Abe decided to postpone the Olympics for a year. The following months provoked numerous discussions on the financial, structural, and personnel problems of the government, while its inadequate approach to combating the disease caused a significant increase in Japanese society`s reluctance to host the Olympic Games even in 2021